Materials handling Functions Influence on Supply Chain Performance of Agricultural Firms Listed on the Nairobi Securities Exchange - Onkangi, Vincent Maina; Odaya, Aleri; Mogwambo, Vitalis Abuga (International Journal of Supply Chain and Logistics, 2026)
Purpose: The study assessed the influence of material handling functions on the supply chain management of agricultural firms listed at the Nairobi Securities Exchange. Methodology: A cross-sectional descriptive survey design was used in the research to target 156 workers from six listed agricultural companies. Questionnaires, interviews, and document analysis were used to gather data, which was then examined using regression models, correlation, and descriptive statistics. Findings: The results showed that Materials Handling also had a significant influence (B = 0.701, p < 0.005), accounting for 32.7% of Supply Chain Management variation. Unique Contribution to Theory, Policy and Practice: From findings, the study concluded that Materials Handling is a strong predictor of Supply Chain Management Performance. Recommendations from the study include, firms should adopt modern Materials Handling practices such as automation and mechanization of materials handling processes. Policymakers should incentivize investments in Materials Handling infrastructure, especially in growing industrial zones.